Analyzing the President Joko Widodo’s International Speech: A Study on Critical Linguistics - Sipri Hanus Tewarat; Sulis Triyono (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2019)
This paper studies President Joko Widodo self-image through his International speech. In order to do so, the researcher use critical linguistics approach proposed by Fowler (1979) that focuses on Halliday’s Systemic Functional namely textual and ideational function. The data source are in the form of the text speech that performed by Joko Widodo in the International Speech at the World Economic ASEAN 2018. The researcher downloaded the data from YouTube in the form of video then transcribed it into the written form. The researcher chooses the data, formulate and take a note based on the aim of the study. The researcher uses Norman Fairclough theory to analyze the data. Based on Halliday’s metafunction, the writer only analyzes based on textual and social practice analyze. The results can be emphasizing that using grammar; it can reveal speaker’s purpose and help in describing argumentative phases in the speech text. On this way, Joko Widodo can build self-image by deliver his industrial program and opinion through appropriate word choice by delivering his industrial program and opinion through appropriate word choice.